Die Landschaft von Maloja (Oberengadin) im Luftbild - Holtmeier, Friedrich-Karl; Lüllau, Ingrid (ERDKUNDE, 1975)
The Autors present an interpretation of an air photograph showing the Maloja Pass region. As a result of geological history the Upper Engadine valley terminates at Maloja Pass without a proper head wall and descends steeply to the Bergell. This orographic gap has a pronounc ed influence on the regional climatic situation. The great difference in elevation causes a distinct vertical zonation of the vegetation, ranging from the subalpine spruce forest to the nival zone. The relief has been glacially moulded. Locally the microrelief conditions conspicuously determine the small scale distribution of the vegetation (e.g. around Maloja village). The uppermost section of the Upper En gadine belongs politically and economically to the Bergell. The small settlements are mostly summer villages of the Bergell communities.